Culture in Post-Crisis Situations : Opportunities for Peacebuilding and Sustainable Recovery - Wrobel, Robert (World Bank, Washington, DC, 2019)
The number of people affected by disasters around the world continues to rise, and countries face recurrent disasters in contexts of conflict and fragility. In 2016 more countries experienced violent conflict than at any time over the past three decades. Much of the recent violence has targeted urban areas and public spaces, and the civilian death toll due to this kind of violent conflict doubled between 2010 and 2016. Extreme poverty is rising in fragile and conflict-affected situations (FCS), and over half of the world’s poor are expected to live in FCS by 2030. Culture plays an important role in building and shaping institutions, and it can do so in both positive and negative ways. Additionally, culture and forms of cultural expression can aid institutions in managing competing interests among different groups in society, including creating spaces for inter-group dialogue and opportunities for inter-group social interaction, or establishing education systems that recognize minority languages of instruction or a plurality of historical narratives. In the pages that follow, this paper will present the case for moving culturally-informed approaches from the margins to the forefront of planning and implementation of post-conflict and post-disaster responses, and offer concrete operational guidance for doing so. Section 2 builds on the case for pursuing a culturally-informed approach in FCS. Section 3 offers guidance for policymakers and operational teams on acquiring and applying a culturally-informed approach in very challenging contexts. Section 4 summarizes several real-world examples in which stakeholders have successfully operationalized a culturally-informed perspective to achieve peace-building and reconstruction objectives. Finally, Section 5 offers some concluding remarks.